Peningkatan Kesehatan Reproduksi Pada Remaja di Era New Normal Melalui Promosi Kesehatan pada Siswa SMA/SMK Seluruh Indonesia - Ira Sukyati; Lucia Firsty; Merida Simanjuntak (Pusat Riset dan Inovasi Nasional, 2022)
Adolescents are an age group that holds the baton for the development of a nation. For this reason, young people need attention. During the COVID-19 pandemic, teenagers are at risk of contracting COVID-19 because of their high activity and tendency to group. In Indonesia, there are 63% of adolescents who have had sexual contact with the opposite sex and 21% have had an abortion, as many as 93.7% of junior high and high school adolescents have done genital stimulation, kissing their partner and oral sex/ and 62.7% of junior high school teenagers who do not virgins Changes in daily activities for adolescents will have an impact on the physical and psychological aspects of adolescents due to social restrictions, such as lack of information related to reproductive health. The purpose of this community service activity is to provide information about adolescent reproductive health online using zoom so that adolescents understand and apply it to their next life. The result of this activity is an increase in the knowledge of adolescents about reproductive health. Through this activity the provision of information about adolescent health can be done periodically.